Association between sociodemographic factors and estrogen receptor-positive, progesterone receptor-positive breast cancer subtypes: A cross-sectional study - Mugada, Vinodkumar; Kolakota, Raj Kiran; Mahato, Varsha (UI Scholars Hub, 2020)
Background: The presence of risk factors have a high risk of developing breast cancer. Our study aimed to find an association between sociodemographic factors and the risk of estrogen receptor (ER)-positive, progesterone receptor (PR)-positive breast cancer among women. Methods: A cross-sectional study was conducted on 200 women with breast cancer. Association between sociodemographic factors and hormone receptor subtypes of breast cancer was found using the Chi-square test. Multiple logistic regression analysis was used to know the strong predictors of hormone receptor subtypes. Results: The mean age was 50.08 (10.67) years. Comorbidities had a statistically significant association with ER-positive subtype (p = 0.007). Body mass index had a statistically significant association with PR-positive subtype (p = 0.042). Comorbidities was found to be the strong independent predictor for ER-positive (OR 2.28; 95% CI: 1.28–4.05, p = 0.003) and PR-positive subtypes (OR 1.78; 95% CI: 1.01–3.13, p = 0.03). Conclusion: We conclude that in our study, body mass index was associated with PR-positive subtype, and comorbidities were associated with ER-positive subtype of breast cancer among the women. Comorbidities remained to be a strong independent predictor of ER-positive and PR-positive subtypes of breast cancer.